KAJIAN GENETIK WARNA BERAS PADI - , KRISTAMTINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Black rice has potential as a source of antioxidants. The results of prevous studies on rice color abroad indicate differences in the inheritance patterns and the number of genes that controll the pigment characters of rice. The differences are thought to be influenced by the choice of parent. This study was conducted to obtain information on the genetic diversity of the argomorphogenetic properties and the total anthocyanin content of local black rice, to study the genetic parameters of the pigment characters of rice, i.e the role of genes and patterns of segregation, to verify the linkage of microsatellite markers with pigment properties of rice and the effectiveness of DNA marker as Marker Assisted Selection on several crosses of black rice with white rice. The experiments were conducted in four stages :1)estimating the genetic diversity and parents selection, 2)establishment of base population through crossing, 3)studying the rice pericarp pigment inheritance and testing of genetic parameters, and 4)verification and use of microsatellite markers of pigment characters and application for Marker Assisted Selection of pericarp pigment. The results of research showed that local of black rice cultivars had broad genetic variability of total anthocyanin content characteristic, b* color parameter and the number of filled grains per panicl, whereas plant height, the number of productive tillers, L* and a * color parameter, leaf width and length, grain length and width, maturity date had narrow genetic variability. The genetic diversity based on microsatellite markers (RM 180, RM 220, RM 224 and RM 252) among black rice cultivars was 28.3 % more than that of white rice cultivars. The grouping based on agromorphogenetic identification and the total anthocyanin content characteristics yielded 2 black rice cultvars i.e. Magelang hairless black rice and Cempo ireng and 2 white rice cultivars i.e. Situbagendit and Inpari 6 selected as parent for artificial crossing. The results of standardized regression analysis, path analysis, and microsatellite markers applicattion as Marker Assisted Selection showed that microstaellite markers (RM220 and RM252) linked with color parameters (L * , a*, b*) and total anthocyanin content. RM 252 microsatellite marker was effective to be used as a selection tool (Marker Assisted Selection) from crosses of black rice and white rice. The character of purple pigment at the crossing between black and white rice was controlled by two mutually complementary dominant genes with recessive epistasis (ratio 9:3:4) which follow the model of additive Ã additive ([m][d][i] and dominant Ã dominant ([m][d][l]) interaction. The action of the gene for the black pigment of rice was perfect dominant which was directed to the parent with purple pericarp pigment (black rice). Key words : black rice, rice pigment, genetics, anthocyanin and microsatellite marker